Monetary and Fiscal Effects on Economic Activity: A Reduced Form Examination of their Relative Importance - Waud, Roger N. (The Review of Economics and Statistics, 1974)
IN recent years there has been a rapidly growing interest in the relative efficacy of monetary policy vis-a-vis fiscal policy as a vehicle for achieving economic stability and regulating economic activity. Several widely discussed empirical studies of this issue have used GNP as the dependent variable in a single-equation least-squares regression with various measures of monetary and fiscal policy as independent variables.' One common objection to this approach is that it is not clear what the structural model is from which this so-called reduced form equation is derived. Another obvious criticism is that the various contemporaneous (as opposed to lagged) measures of fiscal and particularly monetary policy may be significantly influenced by movements in the dependent variable, GNP, thus violating one of the basic assumptions underlying the singleequation least-squares procedure. The major purpose of this paper is to develop and estimate a reduced form which takes some steps toward meeting the above objections, and which hopefully sheds some new light on the relative importance of monetary and fiscal influences on economic activity. By disaggregation and the use of a reduced form framework generically related to that of an earlier study of man-hour behavior (Waud 1968), we seek to reduce the possibility of reverse causation and thereby the problem of single-equation least-squares bias in examining this issue. On the basis of the empirical findings reported here, fiscal influences and monetary influences on economic activity are both significant and appear equally important. Hence our findings are in sharp contrast to those of Andersen and Jordan (1968, 1969), for example, and certainly do not support the contention that monetary influences are much stronger than fiscal influences -a notion which seems to have gained much currency in recent years. In section I the rationale and framework for the analysis is presented. Section II discusses the various measures of monetary and fiscal influences, as well as the problem of bias which may plague studies which use a single-equation least-squares framework to examine the relative importance of monetary and fiscal influences. The estimation of the model is discussed and the results presented in section III. Concluding remarks are made in section IV.